Comparative Study of Early Secondary Nasal Revisions and Costs in Patients With Clefts Treated With and Without Nasoalveolar Molding. Issue 4 (June 2015) - Patel, Parit A.; Rubin, Marcie S.; Clouston, Sean; Lalezaradeh, Frank; Brecht, Lawrence E.; Cutting, Court B.; Shetye, Pradip R.; Warren, Stephen M.; Grayson, Barry H.
<x xml:space="preserve">Abstract</x> Abstract The present study aims to determine the risk of early secondary nasal revisions in patients with complete unilateral and bilateral cleft lip and palate (U/BCLP) treated with and without nasoalveolar molding (NAM) and examine the associated costs of care. A retrospective cohort study from 1990 to 1999 was performed comparing the risk of early secondary nasal revision surgery in patients with a CLP treated with NAM and surgery (cleft lip repair and primary surgical nasal reconstruction) versus surgery alone in a private practice and tertiary level clinic. The NAM treatment group consisted of 172 patients with UCLP and 71 patients with BCLP, whereas the non-NAM-prepared group consisted of 28 patients with UCLP and 5 with BCLP. The risk of secondary nasal revision for patients with UCLP was 3% in the NAM group and 21% in the non-NAM group. The risk of secondary nasal revision for patients with BCLP was 7% in the NAM group compared with 40% in the non-NAM group. Using multicenter averages, the non-NAM revision rates were calculated at 37.8% and 48.5% for U/BCLP, respectively. Applying these risks of revision, NAM treatment led to an estimated savings of between $491 and $4893 depending on the type of cleft. In conclusion, NAM can reduce the number of early secondary nasal revision surgeries and, therefore, reduce the overall cost of care.